2014
DOI: 10.1167/iovs.14-14841
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants Associated With Severe Retinopathy of Prematurity in Extremely Low Birth Weight Infants

Abstract: Citation: Hartnett ME, Morrison MA, Smith S, et al. Genetic variants associated with severe retinopathy of prematurity in extremely low birth weight infants. Invest Ophthalmol Vis Sci. 2014;55:6194-6203. DOI: 10.1167/iovs.14-14841 PURPOSE. To determine genetic variants associated with severe retinopathy of prematurity (ROP) in a candidate gene cohort study of US preterm infants.METHODS. Preterm infants in the discovery cohort were enrolled through the Eunice Kennedy Shriver National Institute of Child Health a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 42 publications
1
38
0
2
Order By: Relevance
“…A US multicenter study from the Neonatal Research Network studied approximately 1,000 infants born with birth weight <1,000 g (extremely low birthweight) and found variants in intronic regions of the gene encoding BDNF associated with severe ROP. 13 Other studies have also found associations with factors within the WNT signaling pathway, including FZD4 , associated with growth impairment and ROP. 14 These findings support the line of thinking that neurovascular connections play a role in the development with ROP.…”
mentioning
confidence: 97%
“…A US multicenter study from the Neonatal Research Network studied approximately 1,000 infants born with birth weight <1,000 g (extremely low birthweight) and found variants in intronic regions of the gene encoding BDNF associated with severe ROP. 13 Other studies have also found associations with factors within the WNT signaling pathway, including FZD4 , associated with growth impairment and ROP. 14 These findings support the line of thinking that neurovascular connections play a role in the development with ROP.…”
mentioning
confidence: 97%
“…(163) Using genetically tested blood spots from infants in the same cohort, variants in the intronic region of the gene BDNF were found in association with severe ROP in extremely low birth weight infants. (74)…”
Section: Advancements In Understanding the Pathophysiology Of Ropmentioning
confidence: 99%
“…(56) Genetic variants in VEGF, EPAS1 (both associated with hypoxia regulation) in members of the WNT signaling pathway (important in development and the disease familial exudative vitreoretinopathy (FEVR))(46, 96) and SOD (encodes superoxide dismutase, an antioxidant enzyme) have been reported in association with any ROP. (74) Members of the WNT pathway have been most commonly found in association with severe ROP. Known mutations of FEVR were associated with intrauterine growth restriction and severe ROP in preterm infants of older gestational ages, suggesting that the presence of FEVR mutations increases the risk of preterm birth and severe ROP in infants who would not have been predicted to develop severe ROP based on degree of prematurity.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several very small studies have found genetic variants in EPAS1, VEGF, SOD, and members of the WNT family in association with ROP. However, a larger study (817 infants and 543 infants in a replication cohort) to determine genetic variants associated with the severe ROP in a candidate gene cohort study of US preterm infants using the whole genome amplified DNA from the stored blood spot samples and the analyses such as, controlled for multiple comparisons, ancestral eigenvalues, family relatedness, and significant epidemiologic variables in both cohorts, showed that only two intronic single-nucleotide polymorphism in the gene BDNF were associated with the severe ROP 85,86…”
Section: Risk Factors For Ropmentioning
confidence: 99%